Interaksi Konfigurasi Politik dan Hukum dalam Rancangan Perubahan Kedua atas Undang-Undang Nomor 30 Tahun 2002 tentang Komisi Pemberantasan Tindak Pidana Korupsi - Abdul Qodir Jaelani (UIN Sunan Kalijaga Yogyakarta, 2015)
This paper discusses the Configuration Interaction Politics and Law in theDraft Second Amendment Act No. 30 of 2002 on the Corruption EradicationCommission. Configuration Interaction is known in the Draft Political and LawSecond Amendment Act No. 30 of 2002 on the Corruption Eradication Commission.If you dig deeper, the rule of law-related legislation and a democratic politicalconfiguration, should the legislation will bring forth legislation that is aspiration. Infact, a lot of cargo Draft Second Amendment Act No. 30 of 2002 on the CorruptionEradication Commission is problematic (not aspiration) in the era of the democraticsystem of Pancasila.